Accelerated Lymph Flow in Early-Stage Secondary Lymphedema Detected by Indocyanine Green Fluorescence Lymphography - Shinaoka, Akira; Koshimune, Seijiro; Yamada, Kiyoshi; Matsumoto, Kumiko; Honda, Masako; Miyake, Maki; Furuichi, Hiromi; Hongo, Atsushi; Kimata, Yoshihiro (Journal of Reconstructive Microsurgery, 2017)
Background The purpose of this study was to evaluate the lymph function of the lower extremities and to identify early symptoms of lymph dysfunction in secondary lymphedema by observing lymph flow with indocyanine green (ICG) fluorescence lymphography (LG).Methods We retrospectively evaluated the lymph flow of 108 limbs in 54 female patients with leg lymphedema secondary to pelvic lymphadenectomy for gynecological carcinoma and 14 limbs in 7 female controls without a history of pelvic lymphadenectomy or radiotherapy. ICG was injected into four points at the distal part of the lower extremity. Lymph flow was evaluated by measuring the proximal point where the ICG could be observed 5 minutes after rest and 15 minutes after a walking exercise.Results In the controls, lymph flow was stable at rest and was well enhanced by exercise. In patients with early-stage lymphedema, lymph flow was already enhanced at rest (p = 0.005) and was further enhanced by exercise. In advanced-stage lymphedema, lymph flow was not enhanced, even by exercise (p = 0.001).Conclusion ICG-LG could evaluate lymph flow and functions of lymph systems and detect accelerated lymph flow in early-stage secondary lymphedema. Detecting accelerated lymph flow may facilitate early detection and treatment of secondary lymphedema.
Keywords: lymphedema; accelerated lymph flow; lymphaticovenous anastomosis